3D failure of a scale-down dry stone retaining wall: A DEM modelling. (15th June 2016) - Quezada, Juan-Carlos; Vincens, Eric; Mouterde, Rémy; Morel, Jean-Claude
Highlights: A down scale test of an idealized road dry stone retaining wall has been created. Concentrated loadings have been placed on the top surface of the backfill. A mixed DEM-continuum modelling of the experiments has been performed. The simulations were able to retrieve the experimental average critical loadings. The mixed DEM-continuum approach seems promising for studying this kind of problem. Abstract: Dry stone retaining walls are vernacular structures that can be found in many places around the world and were mainly built to reduce slope erosion and to allow agricultural practices. Their stability is essentially warranted by the global wall weight and the capacity of individual blocks to develop friction at contact. The arrangement of these hand-placed blocks contributes also to the stability of the wall. A new interest arose in these structures in the last years, first due to the necessity to repair damages inherent to any built heritage, but also to their possible advantages regarding sustainability. Several studies have tried to address the behavior of slope dry stone retaining walls, whereas few conclusive studies have been performed concerning road dry stone retaining walls. In this latter case, the loading implies, apart from the backfill, the existence of a concentrated force on the backfill surface. The failure of such masonry work is accompanied by true three-dimensional deformations. This study is a first attempt to provide a better understanding of the mechanical behavior of road dry stone retaining walls. It involves a small-scale prototype with clay bricks for the wall, and steel blocks, acting as a concentrated loading on the backfill surface at a given distance from the inward wall face. Steel blocks have been superposed until wall failure. A numerical study based on these experiments is then performed by means of a mixed discrete-continuum approach. The numerical model was able to retrieve the average value of the concentrated force triggering failure found in the experiences, except when the concentrated loading is very close to the wall. Nevertheless, the results provided by this study are considered as encouraging even if further work is required to definitely state about the validity of such a numerical technique for the study of actual road dry stone retaining walls.